Manajemen Perubahan Kolaboratif Sebagai Strategi Meningkatkan Daya Saing Organisasi pada Meer Convience Store and Foresthree Coffee Muaro Padang - Fikri, Hasanul; Putri, Erli Azzahra; Apriani, Annisa Eka; Sari, Rahma Kurnia; Putra, Rahmadi Bayu (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
The franchise industry, especially in Indonesia, has grown rapidly in the last few decades. Many local and international franchises compete, causing competitiveness. However, franchise organizations must adopt more innovative and adaptive strategies to maintain their competitiveness. The team carried out activities to find out the competitiveness strategies that have been implemented by partners, namely Meer Convenience Store and Foresthree Coffee as well as the obstacles experienced in implementing change management. The obstacles experienced by partners are resistance to change, lack of effective communication, limited resources, lack of expertise in change management, strong organizational culture that is closed to change, lack of evaluation and monitoring of the change process. With the various obstacles experienced, there is a need for a collaborative change management strategy. In this way, it is hoped that Meer Convenience Store and Foresthree Coffee Muaro Padang will not only be able to survive in a competitive market, but also develop into market leaders who are able to respond to changes quickly and efficiently.